Perceptions of COVID-19 risk among individuals with preexisting health conditions - Holli A. Loomans-Kropp; Mohamed I. Elsaid; Jingbo Yi; Yesung Kweon; Electra D. Paskett (PLoS ONE, 2025)
Objectives To examine the association between the presence of preexisting health conditions (PEC) and the perceived risk of catching COVID-19 at the beginning of the pandemic and assess how risk perceptions changed over time. Methods We used data collected as part of the “Impact of COVID-19” baseline and follow-up surveys to complete our analyses. Participants were interviewed to collect their perceptions of the risk of catching COVID-19 (baseline and follow-up) and the number and type of PEC. Kruskal-Wallis and chi-square tests were used to assess differences in baseline characteristics, and prevalence ratios were estimated using crude and adjusted modified Poisson generalized linear models. Results Of the overall study population, 7,069 participants were eligible for the analysis. The majority (83.7%) of the eligible study population had a history of any PEC. Those with a history of any PEC had a median age of 58 (range: 19–97), were primarily female (67.6%), White non-Hispanic (87.8%), had some college (30.3%), were married or living as married (74.4%), lived in an urban region (67.6%), and reported good (35.4%) or very good (33.9%) health. At baseline, study participants with a history of any PEC were more likely to be concerned about catching COVID-19, using a scale of 0–100, compared to those without PECs (Mean[SD] 60.8[29.8] vs. 53.2[29.7]; p < 0.001), as well as more likely concerned about someone they knew catching COVID-19 (Mean[SD] 70.0[28.8] vs. 64.4[29.4]; p < 0.001). The main effects models showed that self-concern of getting COVID-19 was higher in individuals with any PEC, compared to those with no history of PEC (Prevalence Ratio [PR], 1.15; 95%CI, 1.03–1.29); self-concern was lower at follow-up for those with any PEC, compared to baseline (PR, 0.68; 95%CI, 0.65–0.71). There was evidence of an interaction in the models of concern for self and others, suggesting that one’s perception of risk was influenced by both the presence/absence of PECs and study time points. Conclusions Individuals with PECs perceived a higher risk of COVID-19 infection for themselves and others towards the beginning of the pandemic, although this perception of susceptibility, or risk, was lower at follow-up. In this study, we showed that attitudes toward health and risk of disease of oneself and others may change throughout a pandemic.